Investigating metacognitive writing strategies and writing anxiety in the writing process of ESL writers / Norhartini Aripin - Aripin, Norhartini (2024)
The complexity in writing has caused ESL learners to experience writing anxiety when writing. This language barrier has restricted their writing performance, which results in poor quality compositions. This study therefore aims to identify the types and reasons for writing anxiety, so that professional and practical solutions can be addressed by writing teachers. Moreover, using strategies has been acknowledged as one of coping strategies to deal with writing anxiety. Metacognitive writing strategies are known as a useful writing strategy that can help to regulate and control the writers during planning, monitoring, and evaluating stages. The effectiveness of using metacognitive writing strategies is proven to be beneficial in enhancing self-directed learning, and, in improving their writing performance. Due to the fact that not every ESL writer is equipped with an extensive awareness and wide repertoire of metacognitive writing strategies, the importance of explicitly teaching the strategies should be emphasised. Given the relevance of these issues, the study aims to investigate how the writers use metacognitive writing strategies of Planning, Monitoring and Evaluating during their writing process of expository essays. To accomplish the purposes of this study, a qualitative research design was conducted and data were collected by means of semistructured interview, observation, and think-aloud protocols (TAPs). The participants were six third-semester students of UiTM Pasir Gudang who voluntarily involved in the study. The gathered data were coded and analysed using Atlas-ti (Version 8.0). Findings show that all the participants admitted to experiencing writing anxiety while writing and there were sub-types and sub-reasons of writing anxiety discovered in the study. Another finding obtained in the study was that when employing metacognitive writing strategies, there were sub-categories of the strategies used by the participants during planning, monitoring, and evaluating phases. Thus, these results are in line with those studies which ascertain that strategies can be taught, and that the deployment of metacognitive writing strategies allows learners to have major control over their learning process. A framework of metacognitive writing strategies and writing anxiety is proposed with respect to metacognitive writing strategies used by the participants. Suggestions for future research, and implications for ESL writers and writing teachers are also provided.